Preparation method of modified graphite phase carbon nitride / waterborne polyurethane anticorrosive coating
By introducing polyaniline, chitosan and Hbeta200 modified graphite phase nitride carbon powder into the aqueous polyurethane coating, the CN/PANI/PU, CN/CS/PU and CN/Hbeta200/PU coatings were formed, the CN/PANI/PU, and CN/Hbeta200/PU coatings were solved The problem of failure of traditional coatings improves the corrosion resistance and adhesion of the coating, and achieves efficient metal substrate protection.
Patent Information
- Application Number
- CN202411472320.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-10
AI Technical Summary
Traditional aqueous polyurethane coatings will produce microporous defects and lead to failure on a long-term scale, which will not protect the metal substrate for a long time. The electrochemical activity of PANI decreases with the increase of solution pH, making it difficult to effectively hinder electron transfer.
Polyaniline, chitosan and Hbeta200 are used as carriers to polymerize and grow graphite phase carbon nitride in situ, prepare modified carbon nitride powder, and fill it into aqueous polyurethane emulsion to form CN/PANI/PU and CN /CS/PU and CN/Hbeta200/PU coatings enhance the barrier protection ability of the coating with the help of the passivation mechanism of polyaniline and the dispersibility and hydrophobicity of chitosan and Hbeta200.
The water absorption stability, adhesion and protection efficiency of the coating are significantly improved, ensuring that the adhesion level of the coating is level 1 after 36 hours, and the protection efficiency reaches 86.96%~93.19%. The composite coating is adjusted by adjusting the amount of addition. comprehensive performance.
Smart Images

Figure CN119286377A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of anti-corrosion coatings, and in particular relates to a method for preparing a modified graphite phase carbon nitride / aqueous polyurethane anti-corrosion coating. Background Art
[0002] Corrosion is extremely harmful in all walks of life, and the task of developing environmentally friendly anti-corrosion coatings is becoming increasingly arduous. Although traditional organic coatings, such as waterborne polyurethane, can also protect metal substrates, they themselves will produce microporous defects over a long period of time, leading to failure and cannot protect metal substrates for a long time. Therefore, the barrier protection performance of waterborne polyurethane coatings can be enhanced by introducing a series of graphite phase carbon nitride fillers and taking advantage of the two-dimensional maze effect of graphite phase carbon nitride.
[0003] PANI can undergo reversible redox reactions between different oxidation states. As the pH of the solution increases, the electrochemical activity of PANI will also decrease. At the same time, PANI, like other conjugated polymers, can have a certain conductivity through some doping methods. With the help of the passivation mechanism of polyaniline, the metal surface can generate an electric field in the opposite direction of electron transfer, which may hinder the transfer of electrons from metal to oxidized substances; the loading of chitosan can not only enhance the corrosion resistance of the coating, but also improve the adhesion of the coating, enhance the dispersibility of g-C3N4 in aqueous polyurethane emulsion, and synergistically strengthen the maze effect of g-C3N4; Hbeta 200 The hydrophobicity of molecular sieves due to their high silicon-to-aluminum ratio also helps to synergistically increase the barrier protection ability of g-C3N4. Summary of the invention
[0004] The technical problem to be solved by the present invention is: to provide a method for preparing a modified graphite phase carbon nitride / aqueous polyurethane anti-corrosion coating, and to design three anti-corrosion coatings, one of which uses polyaniline as a carrier, in-situ polymerizes and grows graphite phase carbon nitride to prepare polyaniline modified carbon nitride powder, which is then filled into an aqueous polyurethane emulsion to obtain a CN / PANI / PU coating; one of which uses chitosan as a carrier, originally polymerizes and grows graphite phase carbon nitride to prepare chitosan modified carbon nitride powder, which is then filled into an aqueous polyurethane emulsion to obtain a CN / CS / PU coating; and one of which uses Hbeta 200 As a carrier, originally it was polymerized graphite phase carbon nitride, and Hbeta was prepared 200 Modified carbon nitride powder, which is then filled into waterborne polyurethane emulsion to obtain CN / Hbeta 200 / PU coating. The passivation mechanism of polyaniline can generate an electric field on the metal surface in the opposite direction of electron transfer, which may hinder the transfer of electrons from metal to oxidized substances; chitosan rich in hydroxyl and amino functional groups can enhance the dispersibility of g-C3N4 in aqueous polyurethane emulsion, and can synergistically strengthen the maze effect of g-C3N4; Hbeta 200 The hydrophobicity of molecular sieves due to their high silicon-to-aluminum ratio also helps to synergistically increase the barrier protection ability of g-C3N4.
[0005] The preparation method of modified graphite phase carbon nitride / aqueous polyurethane anti-corrosion coating comprises the following steps:
[0006] Step 1: Grind and clean the iron sheet for testing, and dry it at room temperature for later use;
[0007] Step 2: calcining urea in a muffle furnace to obtain carbon nitride powder, and filling the carbon nitride powder into an aqueous polyurethane emulsion at a mass ratio of 1:400, 1:200, 1:100, and 1:50, sealing the emulsion and stirring it in a magnetic stirrer for 4-6 hours to obtain a graphite phase carbon nitride / aqueous polyurethane anti-corrosion coating;
[0008] Step 3, coating the graphite phase carbon nitride / aqueous polyurethane anti-corrosion coating obtained in step 2 onto the iron sheet obtained in step 1, and obtaining a coating with uniform thickness after curing;
[0009] Step 4: Perform water absorption test, adhesion grade and electrochemical test on the coating obtained in step 3, and determine that the addition ratio of carbon nitride is 0.05g of carbon nitride per 10g of polyurethane emulsion;
[0010] Step 5: Mix g-C3N4 powder and polyaniline liquid in a volume gradient of 2 mL, 3 mL, 4 mL, and 5 mL, stir and disperse for 4 hours, dry and grind to obtain polyaniline-modified carbon nitride powder, and fill it into an aqueous polyurethane emulsion to obtain CN / PANI-x / PU;
[0011] Step 6: Add a certain amount of g-C3N4 powder and chitosan to 1 mL of deionized water according to a mass gradient of CN:CS=10:1, 10:2.5, 10:3, and 10:5, and stir and disperse at room temperature for 4 h. After drying and grinding, chitosan-coated modified carbon nitride powder is obtained, which is then filled into an aqueous polyurethane emulsion to obtain CN / CSx / PU.
[0012] Step 7: In situ thermal polymerization, urea, a carbon nitride precursor, and Hbeta200 molecular sieve were added to each 0.1 g of carbon nitride precursor, respectively. 200Molecular sieves were added to 1 mL of deionized water and stirred for 4 h at room temperature, and then placed in a vacuum oven at 50 ° C to completely dry; after sufficient grinding, the mixture was placed in an intelligent muffle furnace and heated to 520 ° C at a rate of 5 ° C / min and kept warm for 2 h, and then taken out after cooling to room temperature; then washed, centrifuged and dried accordingly to obtain Hbeta 200 Molecular sieve modified carbon nitride powder is filled into waterborne polyurethane emulsion to obtain CN / Hbeta 200 -x / PU.
[0013] The amount of polyaniline added in step 5 is 4 ml.
[0014] In step six, the amount of chitosan added is 0.01-0.5 g.
[0015] The amount of chitosan added in step six is 0.3 g.
[0016] Hbeta as described in step 7 200 The amount of molecular sieve added is 25mg-100mg.
[0017] H-beta as described in step 7 200 The amount of molecular sieve added was 75 mg.
[0018] The preparation method of g-C3N4 powder described in step five and step six is: prepare graphite phase carbon nitride g-C3N4 by a high-temperature calcination method: first weigh urea and put it into a covered ceramic crucible, put it in an intelligent muffle furnace and control the heating rate of 5°C / min according to the program, calcine to 520°C and keep warm for 2h, wait for the product to cool naturally to room temperature and take out; grind the obtained solid, and wash it with deionized water and ethanol in turn to remove unreacted impurities; place the solid after sedimentation in a centrifuge in an oven at 60°C and dry it for 4 to 6 hours to obtain a light yellow g-C3N4 powder.
[0019] Through the above design scheme, the present invention can bring the following beneficial effects:
[0020] 1. The polyaniline-modified carbon nitride / waterborne polyurethane coating prepared by the present invention has a stable water absorption value of 4.46% after 36 hours, an adhesion grade of 1, and log|Z| f =0.01Hz is 3.29Ω·cm 2 , the protection efficiency can reach 86.96%.
[0021] 2. The chitosan-modified carbon nitride / waterborne polyurethane coating prepared by the present invention has a stable water absorption value of 4.75% after 36 hours, an adhesion grade of 1, and log|Z| f =0.01Hz is 3.26Ω·cm 2, the protection efficiency can reach 91.02%.
[0022] 3. Hbeta prepared by the present invention 200 The molecular sieve modified carbon nitride / waterborne polyurethane coating has a stable water absorption value of 5.43% after 36 h, the adhesion grade is 1, and log|Z| f =0.01Hz is 3.30Ω·cm 2 , the protection efficiency can reach 93.19%.
[0023] 4. The modified carbon nitride / waterborne polyurethane coating prepared by the present invention can adjust the comprehensive performance of the CN / PANI / PU composite coating by changing the amount of polyaniline added; the comprehensive performance of the CN / CS / PU composite coating can be adjusted by changing the amount of chitosan added; 200 The amount of CN / Hbeta 200 -x / PU composite coating's comprehensive performance is conducive to the labyrinth effect of two-dimensional nanofillers and increases the protective effect of the composite coating.
[0024] 5. The method of the present invention is optimal for polyaniline, chitosan, Hbeta 200 When the addition amount is greater than 20%, the water absorption rate in the modified carbon nitride / waterborne polyurethane coating is stable at a higher value, the adhesion grade is grade 1, and the protection efficiency is better, so that it can exert excellent anti-corrosion performance and effectively improve the overall performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The present invention is further described below with reference to the accompanying drawings and specific embodiments:
[0026] Figure 1 Fourier transform infrared spectra of CN / PANI, PANI and CN prepared in the embodiments of the present invention.
[0027] Figure 2 This is a graph showing the water absorption (swelling) of the CN / PANI-x / PU (x is 2, 3, 4 and 5) composite coatings and pure 808T polyurethane prepared in the embodiments of the present invention.
[0028] Figure 3 This is a graph showing the adhesion levels of the CN / PANI-x / PU (x is 2, 3, 4 and 5) composite coatings prepared in accordance with the embodiments of the present invention.
[0029] Figure 4 The AC impedance (Nyquist plot) of the CN / PANI-x / PU (x is 2, 3, 4 and 5) composite coatings, pure 808T polyurethane and an uncoated iron sheet prepared in the embodiments of the present invention.
[0030] Figure 5The AC impedance (Bode plot) of the CN / PANI-x / PU (x is 2, 3, 4 and 5) composite coatings, pure 808T polyurethane and an uncoated iron sheet prepared in the embodiments of the present invention.
[0031] Figure 6 Tafel diagrams of the CN / PANI-x / PU (x is 2, 3, 4 and 5) composite coatings, pure 808T polyurethane and uncoated iron sheets prepared in the embodiments of the present invention.
[0032] Figure 7 Fourier transform infrared spectra of CN / CS, CS and CN prepared in the embodiments of the present invention.
[0033] Figure 8 This is a graph showing the water absorption (swelling) of the CN / CSx / PU (x is 10:1, 10:2.5, 10:3 and 10:5) composite coatings and pure 808T polyurethane prepared in accordance with the embodiments of the present invention.
[0034] Fig. 9 This is a graph of adhesion levels of CN / CSx / PU (x is 10:1, 10:2.5, 10:3 and 10:5) composite coatings prepared in embodiments of the present invention.
[0035] Fig.10 The AC impedance (Nyquist plot) of the CN / CSx / PU (x is 10:1, 10:2.5, 10:3 and 10:5) composite coatings, pure 808T polyurethane and an uncoated iron sheet prepared in the embodiments of the present invention.
[0036] Fig.11 The AC impedance (Bode plot) of the CN / CSx / PU (x is 10:1, 10:2.5, 10:3 and 10:5) composite coatings, pure 808T polyurethane and an uncoated iron sheet prepared in the embodiments of the present invention.
[0037] Fig.12 Tafel diagrams of the CN / CSx / PU (x is 10:1, 10:2.5, 10:3 and 10:5) composite coatings prepared in the embodiments of the present invention, pure 808T polyurethane and uncoated iron sheets.
[0038] Fig.13 CN / Hbeta prepared in the embodiment of the present invention 200 , Hbeta 200 and Fourier transform infrared spectra of CN.
[0039] Fig.14 CN / Hbeta prepared in the embodiment of the present invention 200-Water absorption (swelling) graph of x / PU (x is 25, 50, 75 and 100) composite coatings and pure 808T polyurethane.
[0040] Fig.15 CN / Hbeta prepared in the embodiment of the present invention 200 -Graph showing adhesion ratings of x / PU (x is 25, 50, 75 and 100) composite coatings.
[0041] Fig.16 CN / Hbeta prepared in the embodiment of the present invention 200 AC impedance (Nyquist plot) of -x / PU (x is 25, 50, 75 and 100) composite coatings, pure 808T polyurethane and uncoated iron sheet.
[0042] Fig.17 CN / Hbeta prepared in the embodiment of the present invention 200 -AC impedance (Bode plot) of x / PU (x is 25, 50, 75 and 100) composite coating, pure 808T polyurethane and uncoated iron sheet.
[0043] Fig.18 CN / Hbeta prepared in the embodiment of the present invention 200 -Tafel diagram of x / PU (x is 25, 50, 75 and 100) composite coating, pure 808T polyurethane and uncoated iron sheet. DETAILED DESCRIPTION
[0044] In order to better understand the purpose, structure and function of the present invention, the preparation method of a modified graphite phase carbon nitride / aqueous polyurethane anti-corrosion coating of the present invention is further described in detail below in conjunction with the accompanying drawings and tables.
[0045] In a specific embodiment, the experimental conditions of the present invention are as follows:
[0046] Ambient temperature 25°C, 1 atmosphere pressure;
[0047] Polyurethane (PU) is a block copolymer containing urethane bonds (-NH-COO-);
[0048] Urea, molecular weight 60.06 g / mol;
[0049] Water, density 1g / ml, molecular weight 18g / mol;
[0050] Ethanol, density 0.7893 g / ml, molecular weight 46 g / mol;
[0051] Polyaniline (PANI), molecular weight 726.869 g / mol;
[0052] Chitosan (CS), molecular weight 392.46g / mol, also known as deacetylated chitosan, soluble chitin, colorless, odorless, white powder, is a substance rich in hydroxyl and amino functional groups and has biocompatibility.
[0053] Hbeta 200 , molecular weight 302.37g / mol, Hbeta molecular sieve, is a kind of aluminosilicate crystal, a zeolite with a microporous structure, with only pores but no cages, and is a double six-ring crystal cavity composed of two four-membered rings and four five-membered rings.
[0054] The optimal filling ratio is to add 0.05 g of two-dimensional solid nanofiller to every 10 g of waterborne polyurethane liquid phase system coating.
[0055] The graphite phase carbon nitride g-C3N4 is prepared by high-temperature calcination method: first weigh urea and put it into a covered ceramic crucible, put it in an intelligent muffle furnace and control the heating rate of 5℃ / min according to the program, calcine to 520℃ and keep it warm for 2h, wait for the product to cool naturally to room temperature and take it out. Then grind the obtained solid and wash it with deionized water and ethanol in turn to remove unreacted impurities. Finally, place the solid after centrifuge sedimentation in an oven at 60℃ and dry it for 4 to 6 hours to obtain a light yellow g-C3N4 powder.
[0056] The prepared g-C3N4 powder was mixed with a certain amount of polyaniline liquid (2mL, 3mL, 4mL, 5mL by volume gradient), fully dispersed for 4 hours with the help of a magnetic stirrer, and then dried in an oven at 60°C to constant weight. Polyaniline-modified carbon nitride powder was obtained by grinding, and then filled into an aqueous polyurethane emulsion to obtain a CN / PANI-x / PU composite coating.
[0057] A certain amount of prepared carbon nitride powder and a certain amount of chitosan (according to the mass gradient CN:CS = 10:1, 10:2.5, 10:3, 10:5) were added to 1 mL of deionized water and stirred and dispersed at room temperature for 4 hours. Then it was transferred to an oven and completely dried at 60°C. After grinding, chitosan-coated modified carbon nitride powder was obtained, which was then filled into an aqueous polyurethane emulsion to obtain a CN / CSx / PU composite coating.
[0058] The quantitative carbon nitride precursor urea and a certain amount of Hbeta 200 Molecular sieve (mass content is based on adding 25, 50, 75, and 100 mg of Hbeta to every 0.1 g of carbon nitride precursor) 200Molecular sieve), add it to 1mL deionized water, stir and disperse it at room temperature for 4h, and then place it in a vacuum oven at 50℃ until it is completely dry. After sufficient grinding, place the mixture in an intelligent muffle furnace and heat it to 520℃ at a heating rate of 5℃ / min and keep it warm for 2h. Take it out after cooling to room temperature. Then wash, centrifuge and dry it accordingly to get Hbeta 200 Molecular sieve modified carbon nitride powder, which was then filled into waterborne polyurethane emulsion to obtain CN / Hbeta 200 -x / PU composite coating.
[0059] Example 1: Preparation of CN / PANI-2 / PU composite coating
[0060] Mix 0.1 g of g-C3N4 powder and 2 mL of polyaniline liquid (diluted 100 times), fully disperse it for 4 hours with the help of a magnetic stirrer, and then dry it in an oven at 60°C to constant weight. Grind it to obtain polyaniline-modified carbon nitride powder, and then fill it into an aqueous polyurethane emulsion to obtain a CN / PANI-2 / PU composite coating.
[0061] Pure 808T polyurethane and polyurethane with polyaniline modified carbon nitride powder added were used as comparison.
[0062] Example 2: Preparation of CN / PANI-3 / PU composite coating
[0063] Mix 0.1 g of g-C3N4 powder and 3 mL of polyaniline liquid (diluted 100 times), fully disperse it for 4 hours with the help of a magnetic stirrer, and then dry it in an oven at 60°C to constant weight. Grind it to obtain polyaniline-modified carbon nitride powder, and then fill it into an aqueous polyurethane emulsion to obtain a CN / PANI-x / PU composite coating.
[0064] Example 3: Preparation of CN / PANI-4 / PU composite coating
[0065] Mix 0.1 g of g-C3N4 powder and 4 mL of polyaniline liquid (diluted 100 times), fully disperse it for 4 hours with the help of a magnetic stirrer, and then dry it in an oven at 60°C to constant weight. Grind it to obtain polyaniline-modified carbon nitride powder, and then fill it into an aqueous polyurethane emulsion to obtain a CN / PANI-x / PU composite coating.
[0066] Example 4: Preparation of CN / PANI-5 / PU composite coating
[0067] Mix 0.1 g of g-C3N4 powder and 5 mL of polyaniline liquid (diluted 100 times), fully disperse it for 4 hours with the help of a magnetic stirrer, and then dry it in an oven at 60°C to constant weight. Grind it to obtain polyaniline-modified carbon nitride powder, and then fill it into an aqueous polyurethane emulsion to obtain a CN / PANI-x / PU composite coating.
[0068] Example 5: CN / CS (10:1) Preparation of / PU composite coating
[0069] 0.1 g of g-C3N4 powder and 0.01 g of chitosan were added to 1 mL of deionized water and stirred for 4 h at room temperature. Then the mixture was transferred to an oven and dried completely at 60 °C. After grinding, chitosan-coated modified carbon nitride powder was obtained, which was then filled into aqueous polyurethane emulsion to obtain CN / CS (10:1) / PU composite coating.
[0070] Pure 808T polyurethane and polyurethane with chitosan-coated modified carbon nitride powder were used as comparison.
[0071] Example 6: CN / CS (10:2.5) Preparation of / PU composite coating
[0072] 0.1 g of g-C3N4 powder and 0.025 g of chitosan were added to 1 mL of deionized water and stirred for 4 h at room temperature. Then the mixture was transferred to an oven and dried completely at 60 °C. After grinding, chitosan-coated modified carbon nitride powder was obtained, which was then filled into aqueous polyurethane emulsion to obtain CN / CS (10:2.5) / PU composite coating.
[0073] Example 7: CN / CS (10:3) Preparation of / PU composite coating
[0074] 0.1 g of g-C3N4 powder and 0.3 g of chitosan were added to 1 mL of deionized water and stirred for 4 h at room temperature. Then the mixture was transferred to an oven and dried completely at 60 °C. After grinding, chitosan-coated modified carbon nitride powder was obtained, which was then filled into aqueous polyurethane emulsion to obtain CN / CS (10:3) / PU composite coating.
[0075] Example 8: CN / CS (10:5) Preparation of / PU composite coating
[0076] 0.1 g of g-C3N4 powder and 0.5 g of chitosan were added to 1 mL of deionized water and stirred for 4 h at room temperature. Then the mixture was transferred to an oven and dried completely at 60 °C. After grinding, chitosan-coated modified carbon nitride powder was obtained, which was then filled into aqueous polyurethane emulsion to obtain CN / CS (10:5) / PU composite coating.
[0077] Example 9: CN / Hbeta 200 Preparation of -25 / PU composite coating
[0078] 0.1 g of carbon nitride precursor urea and 25 mg of Hbeta 200 Molecular sieves were added to 1 mL of deionized water and stirred for 4 hours at room temperature, and then placed in a vacuum oven at 50°C until completely dried. After sufficient grinding, the mixture was placed in an intelligent muffle furnace and heated to 520°C at a rate of 5°C / min and kept warm for 2 hours. After cooling to room temperature, the mixture was taken out. After washing, centrifugation and drying, Hbeta was obtained. 200 Molecular sieve modified carbon nitride powder, which was then filled into waterborne polyurethane emulsion to obtain CN / Hbeta 200 -25 / PU composite coating.
[0079] Pure 808T polyurethane and added Hbeta 200 Molecular sieve modified carbon nitride powder polyurethane, as a comparison.
[0080] Example 10: CN / Hbeta 200 Preparation of -50 / PU composite coating
[0081] 0.1 g of carbon nitride precursor urea and 50 mg of Hbeta 200 Molecular sieves were added to 1 mL of deionized water and stirred for 4 hours at room temperature, and then placed in a vacuum oven at 50°C until completely dried. After sufficient grinding, the mixture was placed in an intelligent muffle furnace and heated to 520°C at a rate of 5°C / min and kept warm for 2 hours. After cooling to room temperature, the mixture was taken out. After washing, centrifugation and drying, Hbeta was obtained. 200 Molecular sieve modified carbon nitride powder, which was then filled into waterborne polyurethane emulsion to obtain CN / Hbeta 200 -50 / PU composite coating.
[0082] Example 11: CN / Hbeta 200 Preparation of -75 / PU composite coating
[0083] 0.1 g of carbon nitride precursor urea and 75 mg of Hbeta200 Molecular sieves were added to 1 mL of deionized water and stirred for 4 hours at room temperature, and then placed in a vacuum oven at 50°C until completely dried. After sufficient grinding, the mixture was placed in an intelligent muffle furnace and heated to 520°C at a rate of 5°C / min and kept warm for 2 hours. After cooling to room temperature, the mixture was taken out. After washing, centrifugation and drying, Hbeta was obtained. 200 Molecular sieve modified carbon nitride powder, which was then filled into waterborne polyurethane emulsion to obtain CN / Hbeta 200 -75 / PU composite coating.
[0084] Example 12: CN / Hbeta 200 Preparation of -100 / PU composite coating
[0085] 0.1 g of carbon nitride precursor urea and 100 mg of Hbeta 200 Molecular sieves were added to 1 mL of deionized water and stirred for 4 hours at room temperature, and then placed in a vacuum oven at 50°C until completely dried. After sufficient grinding, the mixture was placed in an intelligent muffle furnace and heated to 520°C at a rate of 5°C / min and kept warm for 2 hours. After cooling to room temperature, the mixture was taken out. After washing, centrifugation and drying, Hbeta was obtained. 200 Molecular sieve modified carbon nitride powder, which was then filled into waterborne polyurethane emulsion to obtain CN / Hbeta 200 -100 / PU composite coating.
[0086]
[0087] Table 1
[0088]
[0089] Table 2
[0090]
[0091] Table 3
[0092] Figure 1 The Fourier transform infrared spectra of CN / PANI, PANI and CN prepared in Example 3 of the present invention are shown in Figure 1. As can be seen from the figure, after PANI doping, there is no obvious difference between the infrared spectra of CN / PANI composite materials and PANI and CN, and the peak positions of all samples are the same, which proves that a small amount of doping does not change the chemical structure of g-C3N4. At 800cm -1 The wavenumber at 1200 cm-1 corresponds to the bending vibration of the triazine ring and the stretching vibration of the surface NH bond of g-C3N4. -1 To 1655cm -1The region is the stretching vibration of CN or C=N aromatic heterocycle in g-C3N4. PANI also has peaks at 810cm-1, 1140cm-1, 1488cm-1, etc., corresponding to the CC vibration of benzene ring, N=Q=N stretching vibration (where Q represents quinone ring), and C=C skeleton vibration of phenylenediamine. The characteristic peaks of CN / PANI mixture near 1600cm-1 and 800cm-1 just indicate the successful compounding of the two substances. All the characteristic peaks of pure CN appear in CN / PANI complex, indicating that carbon nitride exists in the sample prepared by thermal polycondensation and the functional groups are not destroyed.
[0093] Figure 2 The water absorption rate (swelling) graph of the CN / PANI-x / PU (x is 2, 3, 4 and 5) composite coatings and pure 808T polyurethane prepared in the embodiments of the present invention. It can be seen from the figure that the water absorption rate of each coating has an increasing trend with the extension of time, and it is maintained at a certain level and reaches a stable state after about 36 hours. For pure 808T polyurethane, its water absorption rate is the highest, which is 6.23%. The water absorption rate of the fillers modified by adding CN / PANI has a significant downward trend. The coating with the lowest water absorption rate is CN / PANI-4 / PU, and the stable value of water absorption after 36 hours is only 4.46%. It is the least likely to swell, and can fully exert its barrier protection effect to prevent the invasion of water molecules and other substances.
[0094] Figure 3 The adhesion grade diagram of the CN / PANI-2 / PU composite coating prepared in Example 1 of the present invention, the CN / PANI-3 / PU composite coating prepared in Example 2, the CN / PANI-4 / PU composite coating prepared in Example 3, and the CN / PANI-5 / PU composite coating prepared in Example 4. It can be seen from the figure that CN / PANI-5 / PU is grade 3, with the greatest degree of shedding and the worst adhesion performance. The adhesion grade classification of the composite coatings of the other three ratios was grade 1 after testing, and the adhesion performance was good.
[0095] Figure 4The AC impedance (Nyquist plot) of the CN / PANI-2 / PU composite coating prepared in Example 1 of the present invention, the CN / PANI-3 / PU composite coating prepared in Example 2, the CN / PANI-4 / PU composite coating prepared in Example 3, the CN / PANI-5 / PU composite coating prepared in Example 4, pure 808T polyurethane and an uncoated iron sheet. As can be seen from the figure, when the volume addition amount of PANI in the four CN / PANI / PU composite coatings increases from 2mL to 5mL, the capacitance arc radius value shows an overall trend of first increasing and then decreasing. For the two coatings CN / PANI-3 / PU and CN / PANI-4 / PU, the capacitance arc radius is significantly larger than that of pure 808T polyurethane (the maximum value of -Z" can reach 1336Ω·cm2), and the composite coating with the largest capacitance arc radius is CN / PANI-4 / PU (the maximum value of -Z" can reach 1993Ω·cm2). The capacitive reactance arc radius of the CN / PANI-2 / PU and CN / PANI-5 / PU coatings is significantly smaller than that of pure 808T polyurethane, which does not reflect the effect of increasing the protective performance on the basis of the original polyurethane coating. Therefore, it is basically determined that the polyaniline modified addition volume within the range of CN / PANI-3 / PU and CN / PANI-4 / PU is a more appropriate coating ratio.
[0096] Figure 5 The AC impedance (Bode plot) of the CN / PANI-2 / PU composite coating prepared in Example 1, the CN / PANI-3 / PU composite coating prepared in Example 2, the CN / PANI-4 / PU composite coating prepared in Example 3, the CN / PANI-5 / PU composite coating prepared in Example 4, pure 808T polyurethane and an uncoated iron sheet. It can be seen from the figure that by calculating the logarithm of the impedance modulus in the low-frequency region log|Z| f = 0.01Hz, it can also be found that the composite coating with the coating ratio of CN / PANI-4 / PU has log|Z| f =0.01Hz has the largest value of 3.29Ω·cm2, which is higher than the 3.21Ω·cm2 of pure 808T polyurethane. This is consistent with the previous results, which can confirm that in the polyaniline-modified carbon nitride / waterborne polyurethane coating system, the CN / PANI-4 / PU composite coating is a coating formula with better anti-corrosion performance.
[0097] Figure 6Table 1 and Table 2 are respectively the Tafel diagrams of the CN / PANI-2 / PU composite coating prepared in Example 1 of the present invention, the CN / PANI-3 / PU composite coating prepared in Example 2, the CN / PANI-4 / PU composite coating prepared in Example 3, the CN / PANI-5 / PU composite coating prepared in Example 4, pure 808T polyurethane and an uncoated iron sheet, and the Tafel polarization curve fitting data table of the four CN / PANI / PU composite coatings. It can be seen from the figure and the table that after the CN / PANI solid filler is added to the PU emulsion, the corrosion potential E corr There is a clear increasing trend. Uncoated tinplate sheet E corr The value is the smallest, which is -0.9610V, and has a greater tendency to corrosion. corr As the volume of polyaniline added changes from 2 mL to 5 mL, E corr The value also increased from -0.8092V to -0.7803V. This can be used as a basis for the transformation of the anti-corrosion mechanism after adding polyaniline to the composite coating system to mainly affect the potential E. corr The calculated protection efficiency η also shows that the protection efficiency η of the four CN / PANI / PU composite coatings does not significantly exceed 90%. For coating No. 5, the protection efficiency of the CN / PANI-2 / PU composite coating is even only 78.58%. This is mainly because the addition of conductive polyaniline will first promote the flow of electrons through its excellent conductive properties. After reaching a certain level, a passivation film is formed on the metal surface, which in turn affects the potential E and thus inhibits the occurrence of corrosion.
[0098] Figure 7 The Fourier transform infrared spectra of CN / CS, CS and CN prepared in Example 7 of the present invention are shown in Figure 1. As can be seen from the figure, after CS doping, there is no obvious difference between the infrared spectra of the CN / CS composite material and CS and CN, and the peak positions of all samples are the same, which proves that a small amount of doping does not change the chemical structure of g-C3N4. At 800cm -1 The wavenumber at 1200 cm-1 corresponds to the bending vibration of the triazine ring and the stretching vibration of the surface NH bond of g-C3N4. -1 To 1655cm -1 The region is the stretching vibration of CN or C=N aromatic heterocyclic ring in g-C3N4. The 3402cm -1 -OH vibration peak, 2923cm -1 The -CH vibration peak and 1604cm -1The CN / CS mixed solid filler also has relevant peaks at these corresponding positions, and it can be found that the CN / CS mixture has a peak at 800 cm -1 The unique triazine ring bending vibration peak of CN and the characteristic peak of pure CN also appeared nearby, indicating that carbon nitride existed in the sample prepared by thermal polycondensation and the functional group was not destroyed. All these just indicate the successful compounding and synthesis of CN / CS mixed solid filler.
[0099] Figure 8 CN / CS prepared in Example 5 of the present invention (10:1) / PU composite coating, CN / CS prepared in Example 6 (10:2.5) / PU composite coating, CN / CS prepared in Example 7 (10:3) / PU composite coating, CN / CS prepared in Example 8 (10:5) / PU composite coating, and pure 808T polyurethane water absorption (swelling) graph. As can be seen from the figure, the basic trend of water absorption is still to increase first, and basically remain stable after about 36 hours, and the water absorption of the four modified composite coatings is lower than that of pure 808T polyurethane, showing better anti-swelling properties. Among the four coatings, the ratio of CN:CS in the mixed solid filler added to the PU coating is different, but the water absorption is basically stable at about 4.51±0.24%, and the difference is not obvious.
[0100] Fig. 9 CN / CS prepared in Example 5 of the present invention (10:1) / PU composite coating, CN / CS prepared in Example 6 (10:2.5) / PU composite coating, CN / CS prepared in Example 7 (10:3) / PU composite coating, CN / CS prepared in Example 8 (10:5) Adhesion grade of CN / CS / PU composite coating. As can be seen from the figure, the adhesion grade of CN / CS / PU composite coating is stable at grade 1, and the adhesion performance is relatively good. This is mainly because the large number of amino groups and hydroxyl groups of chitosan can fully increase the crosslinking degree of mixed solid filler and PU after modification of carbon nitride, so that the adhesion performance is relatively good at grade 1.
[0101] Fig.10 CN / CS prepared in Example 5 of the present invention (10:1) / PU composite coating, CN / CS prepared in Example 6 (10:2.5) / PU composite coating, CN / CS prepared in Example 7 (10:3) / PU composite coating, CN / CS prepared in Example 8 (10:5)The AC impedance (Nyquist plot) of CN / CS composite coating, pure 808T polyurethane and uncoated iron sheet. As can be seen from the figure, the composite coating with a significantly increased capacitive arc radius and greater than that of pure 808T polyurethane coating is CN / CS. (10:3) / PU、CN / CS (10:5) / PU are two composite coatings, and the one with the largest capacitive reactance arc radius is CN / CS (10:3) / PU composite coating. It shows that when the ratio of CN:CS is 10:3, CN / CS (10:3) / PU composite coating has good anti-corrosion performance.
[0102] Fig.11 CN / CS prepared in Example 5 of the present invention (10:1) / PU composite coating, CN / CS prepared in Example 6 (10:2.5) / PU composite coating, CN / CS prepared in Example 7 (10:3) / PU composite coating, CN / CS prepared in Example 8 (10:5) / PU composite coating, pure 808T polyurethane and uncoated iron sheet AC impedance (Bode plot). It can be seen from the figure that the logarithm of the impedance modulus in the low-frequency region log|Z| f =0.01Hz The maximum is also CN / CS (10:3) / PU coating, 3.26Ω·cm2, higher than the 3.21Ω·cm2 value of pure 808T polyurethane. This shows that the introduction of more chitosan in carbon nitride solid filler does not significantly increase the charge transfer resistance and anti-corrosion performance of the modified polyurethane coating. (10:3) / PU composite coating has good anti-corrosion performance.
[0103] Fig.12 Table 2 and Table 3 are respectively CN / CS prepared in Example 5 of the present invention. (10:1) / PU composite coating, CN / CS prepared in Example 6 (10:2.5) / PU composite coating, CN / CS prepared in Example 7 (10:3) / PU composite coating, CN / CS prepared in Example 8 (10:5) Tafel plots of CN / CS / PU composite coatings, pure 808T polyurethane and uncoated iron sheet and Tafel polarization curve fitting data table of four CN / CS / PU composite coatings. It can be seen from the figure and table that the protection efficiency of the four CN / CS / PU composite coatings is significantly increased compared with pure 808T polyurethane, among which CN / CS (10:3) / PU、CN / CS (10:5) The protection efficiency η of both PU and PU coatings can reach more than 90%, which has obvious advantages in reducing the corrosion current density. corrAccording to the test results, the corrosion potential E corr There is also a clear increasing trend (moving to the right on the x-axis).
[0104] Fig.13 CN / Hbeta prepared in Example 11 of the present invention 200 -75, Hbeta 200 Fourier transform infrared spectra of and CN. It can be seen from the figure that at 800cm -1 The wavenumber at 1200 cm-1 corresponds to the bending vibration of the triazine ring and the stretching vibration of the surface NH bond of g-C3N4. -1 To 1655cm -1 The region is the stretching vibration of CN or C=N aromatic heterocycle in g-C3N4. Hbeta200 has a characteristic peak near 1100cm-1, which is mainly caused by the asymmetric stretching vibration inside the molecular sieve hybrid tetrahedron. CN / Hbeta200 solid filler also has similar characteristic peaks in these regions, and the characteristic peak of pure CN appears, indicating that carbon nitride exists in the sample prepared by thermal polycondensation, and the functional group is not destroyed, confirming the successful mixing of the two substances.
[0105] Fig.14 CN / Hbeta prepared in 9 examples of the present invention 200 -25 / PU composite coating, CN / Hbeta prepared in Example 10 200 -50 / PU composite coating, CN / Hbeta prepared in Example 11 200 -75 / PU composite coating, CN / Hbeta prepared in Example 12 200 -100 / PU composite coating and pure 808T polyurethane water absorption (swelling) diagram. It can be seen from the figure that the water absorption still shows an increasing trend in the first 24 hours, and basically remains stable after the 36th hour. Among the four modified coatings of the present invention, the one with the smallest water absorption after 36 hours of stability is CN / Hbeta 200 -50 / PU composite coating, its water absorption rate is G x The value is 5.17%, while the minimum water absorption of the CN / PANI / PU and CN / CS / PU composite coatings are 4.46% and 4.51%, respectively. 200 ) The water absorption performance of the modified carbon nitride / waterborne polyurethane coating is worse than that of the first two modification methods. This is mainly due to the adsorption of water molecules caused by some pore structures in the molecular sieve. However, since carbon nitride is used as the main filling material, CN / Hbeta 200 The water absorption rate of solid fillers refilled into waterborne polyurethane emulsion is still lower than that of pure 808T polyurethane coating.
[0106] Fig.15 CN / Hbeta prepared in 9 examples of the present invention 200 -25 / PU composite coating, CN / Hbeta prepared in Example 10 200 -50 / PU composite coating, CN / Hbeta prepared in Example 11 200 -75 / PU composite coating, CN / Hbeta prepared in Example 12 200 -100 / PU composite coating adhesion grade diagram. It can be seen from the figure that only CN / Hbeta 200 -75 / PU, CN / Hbeta 200 -100 / PU composite coatings showed good adhesion and were graded as 1. The other two coatings had relatively more coating shedding in the sliding grid test and relatively poor mechanical properties. This shows that CN / Hbeta 200 -75 / PU, CN / Hbeta 200 -100 / PU has better adhesion.
[0107] Fig.16 CN / Hbeta prepared in 9 examples of the present invention 200 -25 / PU composite coating, CN / Hbeta prepared in Example 10 200 -50 / PU composite coating, CN / Hbeta prepared in Example 11 200 -75 / PU composite coating, CN / Hbeta prepared in Example 12 200 -100 / PU composite coating, pure 808T polyurethane and uncoated iron sheet AC impedance (Nyquist plot). It can be seen from the figure that only CN / Hbeta 200 The capacitive reactance arc radius of the composite coating of -75 / PU has a tendency to increase compared with the pure 808T polyurethane coating. 200 The / PU composite coating only has a larger capacitance arc radius than the uncoated iron sheet, and does not show a better physical barrier effect. This shows that the CN / Hbeta 200 -75 / PU has the largest radius and the highest impedance value, the electron transfer resistance increases, and the interface charge transfer resistance increases, which means that under light irradiation, CN / Hbeta 200 -75 / PU charge transfer slows down.
[0108] Fig.17 CN / Hbeta prepared in 9 examples of the present invention 200 -25 / PU composite coating, CN / Hbeta prepared in Example 10 200 -50 / PU composite coating, CN / Hbeta prepared in Example 11200 -75 / PU composite coating, CN / Hbeta prepared in Example 12 200 -100 / PU composite coating, pure 808T polyurethane and uncoated iron sheet AC impedance (Bode plot). It can be seen from the figure that CN / Hbeta 200 -75 / PU composite coating log|Z| f =0.01Hz value is the maximum characteristic.
[0109] Fig.18 Table 2 and Table 3 are CN / Hbeta obtained by implementing 9 examples of the present invention. 200 -25 / PU composite coating, CN / Hbeta prepared in Example 10 200 -50 / PU composite coating, CN / Hbeta prepared in Example 11 200 -75 / PU composite coating, CN / Hbeta prepared in Example 12 200 Tafel plots of CN / Hbeta200 / PU composite coating, pure 808T polyurethane and uncoated iron sheet and Tafel polarization curve fitting data table of four CN / Hbeta200 / PU composite coatings. 200 / PU composite coating according to the corrosion current density log i corr The calculated protection efficiency η values are all greater than 90%, which is better than the effects of the first two modification methods. This is mainly because Hbeta 200 As aluminosilicate crystals, molecular sieves have weak electrical conductivity and can block electrons. Therefore, the protection efficiency η value is relatively large. corr From the perspective of corrosion potential, the two composite coatings with the largest corrosion potential are CN / Hbet a200 -25 / PU, CN / Hbeta200-75 / PU, the values are -0.6417V, -0.6923V respectively. In comparison, the coatings of these two formulations have a smaller corrosion tendency and can protect the tinplate sheet. This shows that the Hbeta 200 In the molecular sieve modified carbon nitride / waterborne polyurethane coating system, CN / Hbeta 200 -75 / PU is the formula ratio with better anti-corrosion coating performance.
[0110] In summary, the present invention uses polyaniline as a carrier, originally polymerized graphite phase carbon nitride, to prepare polyaniline modified carbon nitride powder, which is then filled into an aqueous polyurethane emulsion to obtain a CN / PANI / PU coating; uses chitosan as a carrier, originally polymerized graphite phase carbon nitride, to prepare chitosan modified carbon nitride powder, which is then filled into an aqueous polyurethane emulsion to obtain a CN / CS / PU coating; and uses Hbeta 200 As a carrier, originally it was polymerized graphite phase carbon nitride, and Hbeta was prepared 200 Modified carbon nitride powder, which is then filled into waterborne polyurethane emulsion to obtain CN / Hbeta 200 / PU coating. The passivation mechanism of polyaniline can generate an electric field on the metal surface in the opposite direction of electron transfer, which may hinder the transfer of electrons from metal to oxidized substances; chitosan rich in hydroxyl and amino functional groups can enhance the dispersibility of g-C3N4 in aqueous polyurethane emulsion, and can synergistically strengthen the maze effect of g-C3N4; Hbeta 200 The hydrophobicity of molecular sieves due to their high silicon-aluminum ratio is also beneficial to synergistically increase the barrier protection ability of g-C3N4, thereby improving the anti-corrosion performance.
[0111] It is to be understood that the present invention is described by some embodiments, and it is known to those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application are within the scope of protection of the present invention.
Claims
1. A method for preparing a modified graphite phase carbon nitride / aqueous polyurethane anticorrosion coating, characterized in that: The following steps are included: Step 1: Grind and clean the iron sheet for testing, and dry it at room temperature for later use; Step 2: calcining urea in a muffle furnace to obtain carbon nitride powder, and filling the carbon nitride powder into an aqueous polyurethane emulsion at a mass ratio of 1:400, 1:200, 1:100, and 1:50, sealing the emulsion and stirring it in a magnetic stirrer for 4-6 hours to obtain a graphite phase carbon nitride / aqueous polyurethane anti-corrosion coating; Step 3, coating the graphite phase carbon nitride / aqueous polyurethane anti-corrosion coating obtained in step 2 onto the iron sheet obtained in step 1, and obtaining a coating with uniform thickness after curing; Step 4: Perform water absorption test, adhesion grade and electrochemical test on the coating obtained in step 3, and determine that the addition ratio of carbon nitride is 0.05g of carbon nitride per 10g of polyurethane emulsion; Step 5: Mix g-C3N4 powder and polyaniline liquid in a volume gradient of 2 mL, 3 mL, 4 mL, and 5 mL, stir and disperse for 4 hours, dry and grind to obtain polyaniline-modified carbon nitride powder, and fill it into an aqueous polyurethane emulsion to obtain CN / PANI-x / PU; Step 6: Add a certain amount of g-C3N4 powder and chitosan to 1 mL of deionized water according to a mass gradient of CN:CS=10:1, 10:2.5, 10:3, and 10:5, and stir and disperse at room temperature for 4 h. After drying and grinding, chitosan-coated modified carbon nitride powder is obtained, which is then filled into an aqueous polyurethane emulsion to obtain CN / CSx / PU. Step 7: In situ thermal polymerization, urea, a carbon nitride precursor, and Hbeta200 molecular sieve were added to each 0.1 g of carbon nitride precursor, respectively. 200 Molecular sieves were added to 1 mL of deionized water and stirred for 4 h at room temperature, and then placed in a vacuum oven at 50 ° C to completely dry; after sufficient grinding, the mixture was placed in an intelligent muffle furnace and heated to 520 ° C at a rate of 5 ° C / min and kept warm for 2 h, and then taken out after cooling to room temperature; then washed, centrifuged and dried accordingly to obtain Hbeta 200 Molecular sieve modified carbon nitride powder is filled into waterborne polyurethane emulsion to obtain CN / Hbeta 200 -x / PU.
2. The method for preparing the modified graphite phase carbon nitride / aqueous polyurethane anticorrosive coating according to claim 1, characterized in that: The amount of polyaniline added in step 5 is 4 ml.
3. The method for preparing the modified graphite phase carbon nitride / aqueous polyurethane anticorrosive coating according to claim 1, characterized in that: In step six, the amount of chitosan added is 0.01-0.5 g.
4. The method for preparing the modified graphite phase carbon nitride / aqueous polyurethane anticorrosive coating according to claim 1, characterized in that: The amount of chitosan added in step six is 0.3 g.
5. The method for preparing the modified graphite phase carbon nitride / aqueous polyurethane anticorrosive coating according to claim 1, characterized in that: Hbeta as described in step 7 200 The amount of molecular sieve added is 25mg-100mg.
6. The method for preparing the modified graphite phase carbon nitride / aqueous polyurethane anticorrosive coating according to claim 1, characterized in that: H-beta as described in step 7 200 The amount of molecular sieve added was 75 mg.
7. The method for preparing the modified graphite phase carbon nitride / aqueous polyurethane anticorrosive coating according to claim 1, characterized in that: The preparation method of g-C3N4 powder described in step five and step six is: prepare graphite phase carbon nitride g-C3N4 by a high-temperature calcination method: first weigh urea and put it into a covered ceramic crucible, put it in an intelligent muffle furnace and control the heating rate of 5°C / min according to the program, calcine to 520°C and keep warm for 2h, wait for the product to cool naturally to room temperature and take out; grind the obtained solid, and wash it with deionized water and ethanol in turn to remove unreacted impurities; place the solid after sedimentation in a centrifuge in an oven at 60°C and dry it for 4 to 6 hours to obtain a light yellow g-C3N4 powder.
Citation Information
Patent Citations
Polyaniline-carbon nitride compound, resin composite coating and preparation method thereof
CN115926522A
Preparation method of H-Beta molecular sieve / carbon nitride nano composite material
CN116984022A
Cited By
High-silicon zeolite / carbon nitride / polyurethane anticorrosive paint as well as preparation method and application thereof
CN120025730A
High-silica zeolite / carbon nitride / polyurethane anti-corrosion coating and its preparation method and application
CN120025730B